Pyrolytic Oil Yield from Waste Plastic in Quezon City, Philippines: Optimization Using Response Surface Methodology - Olalo, Joselito Abierta (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Plastics play an essential role in packaging materials because of their durability to different environmental conditions. With its importance in the community lies the problem with waste disposal. Plastic is a non-biodegradable material, making it a big problem, especially when thrown in dumpsites. In solving the plastic problem, one efficient way to reduce its volume is through thermal processing such as pyrolysis. This study used the pyrolysis method to recover energy from plastic waste. Liquid oil from plastic was comparable to regular fuel used in powering engines. Before the pyrolysis process, a 3k factorial Box-Behnken Design was used in determining the number of experiments to be used. The output oil yield in each pyrolysis runs was optimized in different parameters, such as temperature, residence time, and particle size using response surface methodology to determine the optimum oil yield. Between polyethylene (PE), mixed plastic, and polystyrene (PS), PS produced its highest oil yield of 90 %. In comparison, mixed plastic produced only its highest oil yield of 45 % in 500 ºC temperature, 120 min residence time, and 3 cm particle size. The produced quadratic mathematical models in PE, mixed, and PS plastic were significant in which the p-values were less than 0.05. Using mathematical models, the optimum oil yield for PE (467.68 ºC, 120 min residence time, 2 cm particle size), mixed (500 ºC, 120 min residence time, 2.75 cm particle size) and PS plastic (500 ºC, 120 min residence time, 2 cm particle size) were 75.39 %, 46.74 %, and 91.38 %, respectively